Sexual abuse of girls in Oaxaca: legal or cultural problem? (Revista Innova Educación, 2021)
The article analyzed the problem of child sexual violence in the state of Oaxaca, Mexico. The methodology was qualitative based on analysis of documents (empirical studies, legislation and hemerography) and complemented with descriptive statistics. It is found that: legislation has been harmonized with national and international law, legal and applicability vacancies persist, bureaucratic processes, access to justice for victims, impunity and the absence of real statistics; the highest incidence is in the house and the school, being the principal aggressors of the family and teachers. The legal advance is the most significant, yet it does not recover the cultural diversity of the State. It is concluded that, in addition to a legal and cultural problem, constituting systemic, institutional and symbolic violence.
Keywords: Child sexual abuse; sexual violence; institutional violence; symbolic violence; Oaxaca